Kinetics and Equilibrium Study of Cadmium Ion Sorption onto Date Pits — An Agricultural Waste - Fawzi Banat; Sameer Al-Asheh; Leema Al-Makhadmeh (Adsorption Science & Technology)
Activated carbons derived from date pits obtained as a surplus agricultural solid waste and natural date pits were used for the adsorption of cadmium ions from water. The effect of contact time, pH, temperature, cadmium ion concentration, sorbent dose, salinity, as well as the activation temperature on the removal of cadmium ions by date pits was studied. The maximum adsorption capacity of date pits for cadmium ions was obtained using the linear Langmuir isotherm model and used as a basis for comparative purposes. Three sorption kinetic models were used for explaining the probable mechanisms of cadmium ion uptake. The kinetic data for the adsorption process obeyed a second-order rate equation.